Meningkatkan Hasil Belajar Siswa dengan Pemberian Scaffolding pada Materi Larutan Elektrolit dan Nonelektrolit - Nathania Aghata; Ayi Darmana; Haqqi Annazili Nasution (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to improve student learning outcomes through the application of the scaffolding method to the topic of electrolyte and nonelectrolyte solutions in grade XI students of SMA Negeri 14 Medan. The research was motivated by the low student learning outcomes due to the use of conventional learning methods that lack student engagement. This study was a Classroom Action Research (CAR) conducted in two cycles, covering the planning, implementation, observation, and reflection stages, with 30 grade XI students as subjects. Data collection techniques were carried out through tests (pre-test and post-test) and observation, while data analysis used N-Gain. The results showed an increase in student learning outcomes, where in the first cycle the N-Gain value was 0.6 (moderate category) and increased in the second cycle to 0.73 (high category). In addition, student engagement in the learning process also increased. Thus, the application of the scaffolding method is effective in improving learning outcomes by providing gradual assistance and student engagement in the topic of electrolyte and nonelectrolyte solutions.